2013
DOI: 10.1002/pssa.201330164
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of electrical characteristics in the solution‐processed nanocrystalline indium oxide thin‐film transistors depending on yttrium doping concentration

Abstract: (0,6,12, or 20 mol%)-doped In 2 O 3 (YInO; YIO) thin films were fabricated by the sol-gel spin-coating technique, and they were used as the active layer of thin-film transistor (TFT) devices. The YIO-TFTs operate in the n-channel enhancement mode and exhibit a well-defined pinch-off and saturation region. The Y 3þ (12 mol%)-doped In 2 O 3 TFT possesses the optimal performance, and its field-effect mobility in the saturated regime, threshold voltage, on-off ratio, and S factor are 0.95 cm 2 V À1 s À1 , 6.74 V, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The XPS spectra of In 3d peaks of In-Yb-O thin films with different Yb ratios were shown in Figure 5 b. The In peaks located at binding energies of 451.4 eV (In 3d 3/2 ) and 443.9 eV (In 3d 5/2 ) suggest the presence of In-O bonding [ 19 ]. With the Yb ratio increases, the In peak shifts toward a lower binding energy direction owing to stronger Yb-O binding strength (387 kJ/mol) than that of In-O (320 kJ/mol) [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XPS spectra of In 3d peaks of In-Yb-O thin films with different Yb ratios were shown in Figure 5 b. The In peaks located at binding energies of 451.4 eV (In 3d 3/2 ) and 443.9 eV (In 3d 5/2 ) suggest the presence of In-O bonding [ 19 ]. With the Yb ratio increases, the In peak shifts toward a lower binding energy direction owing to stronger Yb-O binding strength (387 kJ/mol) than that of In-O (320 kJ/mol) [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The great difference in electronegativity between dopant and oxygen contributes to a strong metal-oxygen bond [ 18 ]. The SEP is considered as the main parameter to evaluate the ability of dopant to bind oxygen [ 19 ]. The metal-oxide dissociation energy is defined as the standard enthalpy change in reaction to the bond breaking.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, metal oxide TFTs are generally grown by vacuum-based technologies such as radio frequency (RF) magnetron sputtering, atomic layer deposition, or pulse laser deposition. Compared with the conventional approaches, solution processing has been actively studied owing to its low cost, large-area deposition capability, equipment simplicity, and ease in control of the composition ratio of each precursor. ,, Solution processing initially focused on organic solvent, which is toxic to human beings and harmful to the environment. Fortunately, the recently developed aqueous solution processing is considered to be a safe and effective method for green oxide electronics …”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the local environment remains almost unchanged with increasing B doping concentrations. However, the In peak gradually shifts toward low binding energy, which is, on the one hand, due to due to the bonding strength of B-O (808 kJ/mol) being stronger than that of In-O (346 kJ/mol), and on the other hand because B doping can reduce oxygen vacancy-related defects, resulting in a denser atomic stacking and enhanced electron shielding between adjacent atoms [ 25 , 26 , 27 ]. Figure 3 c presents the XPS spectra of B 1s with different B contents.…”
Section: Resultsmentioning
confidence: 99%